AKTIVISME POLITIK BADAN KOORDINASI PERCEPATAN PEMBENTUKAN KABUPATEN CIBALIUNG (BAKOR P2KC) DALAM MENGADVOKASI PEMEKARAN WILAYAH DI KABUPATEN PANDEGLANG - Shakila Humaira; Mahpudin Mahpudin; Bunga Natasya; Ariestawidya Kinasih Azzahra (Jurnal Kebijakan Pembangunan Daerah, 2025)
Territorial expansion is a significant phenomenon in Indonesia's administrative and political context, often emerging as a response to the public's need for better public services and more efficient resource management. This study describes the processes and challenges in the effort to establish Cibaliung Regency as a concrete example of local autonomy aspirations. Through an analysis of territorial coalitions and political dynamics, this research highlights the role of political actors, such as local community organizations and regional governments, in forming alliances to achieve territorial expansion goals. The desire of the Cibaliung community to become an autonomous region is driven by several factors, including challenges in accessing public services and perceptions of unequal development. The region's significant economic and tourism potential also serves as a major incentive for territorial expansion. However, the expansion process faces significant obstacles, including the national moratorium that has halted most expansion proposals in Indonesia, as well as bureaucratic challenges and complex political competition. This study identifies that while territorial expansion promises substantial benefits for more effective local governance, this approach also poses risks to the economic stability of the parent region and social integration in the newly formed area. The social, economic, and legal implications of territorial expansion must be carefully managed to minimize negative impacts and maximize positive benefits for all stakeholders involved.